Defining the Industrial and Engineering Management Professional Profile: a longitudinal study based on job advertisements - Rui Manuel Lima; Diana Mesquita; Carla Rocha; Mauro Rabelo (Production)
Abstract The engineering professional profiles have been discussed by several branches of the engineering field. On the one hand, this discussion helps to understand the professional practice and contributes to the specification of the competences that are suitable for each function and company culture. On the other hand, it is an essential starting point for the definition of curricula in engineering schools. Thus, this study aims to characterize, in an innovative way based on job advertisements, the demand for competences and areas of practice for Industrial Engineering and Management contributing for the definition of a professional profile. This characterization is based on the analysis of 1391 job advertisements, collected during seven years from a Portuguese newspaper. The data analysis takes into account the job description in which two categories were considered: areas of professional practice (e.g. project management) and transversal competences (e.g. teamwork). Considering the total number of job advertisements, it was possible to identify 1,962 cumulative references for 11 professional practice areas and 5,261 cumulative references for transversal competences. The contribution of this study lies on the identification of the main areas of practice and the main transversal competences demanded by employers.